Hutan Dibabat, Masyarakat Melarat, Masa Depan Gelap Refleksi Teologis atas Keberpihakan Gereja Terhadap Masyarakat dalam Upaya Pelestarian Alam - I Ketut Gegel (Studia Philosophica et Theologica, 2019)
The Dayak community is known as a community that is close to nature, and even, can be said they unite themselves with nature. Nature is a "home" for shelter, a "pool" for fishing and Savannah for hunting wilds animals. Short words, nature is a treasure that is not counted in their lives. Therefore, when nature was damaged by investors for mining and coconut palm plantation businesses, the Dayak community was faced with great difficulties to maintain the sustainability for their own lives, because the nature that sustains their lives today has been damaged and destroyed. The critical question that arises: "How to deal with this challenge and who should help them fight for their rights in the face of greedy investors?” Fighting alone, should be difficult, because they should faced not only investors, but also by two other forces, namely: security authorities and local authorities. For this reason, other institutions are needed to help overcome this difficulty. The Catholic Church is an institution which present among Dayak community and together with them, fighting and protect their rights and lives. The Church's partisanship is a clear evidence of the embodyment of its main mission, that is, proclaiming the Goos News for the people. This noble task, merely, does not layed down in the act of liturgical cult, but also in real action, in concrete actions to fight for the rights, freedoms and the goodness of human life. Through these actions, the Church presents salvation to human being. Of course, the effort and commitment to ptotect local community and nature will produce more a good and better result when done together with other institutions. Therefore, Pope Francis through his Encyclical Letter Laudato Si, invites all parties who are well-wished to be jointly involved in seeking salvation for everyone through concrete efforts, that is, to protect the earth, our common home.